БОШЛАНҒИЧ СИНФ ОНА ТИЛИ ДАРСЛАРИДА ЛИНГВИСТИК КОМПЕТЕНЦИЯНИ ШАКЛЛАНТИРИШНИНГ НАЗАРИЙ АСОСЛАРИ - Тажбенова, С.С. (SCIENCE and SOCIETY, 2023)
This article highlights the theoretical foundations of scientific research aimed at developing literacy, speech culture, linguistic competence and the essence of students’ linguistic competence in native language lessons in primary school.